2020
DOI: 10.1097/iae.0000000000002395
|View full text |Cite
|
Sign up to set email alerts
|

Ridge-Shaped Macula in Young Myopic Patients and Its Differentiation From Typical Dome-Shaped Macula in Elderly Myopic Patients

Abstract: Purpose: To assess and compare clinical features of a ridge-shaped macula (defined as macular elevation only in one meridian across the fovea) in individuals younger than 20 years with those of a dome-shaped macula (DSM) in patients aged 20+ years. Methods: The retrospective observational case series study included 185 highly myopic eyes of 100 consecutive patients younger than 20 years, who were compared with highly myopic patients with DSMs, aged 20+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 27 publications
4
46
1
1
Order By: Relevance
“…Thus, it is possible that our patients were within the spectrum of ridge-shaped macula. However, there were several differences between the present study and the study by Xu et al [13]. In the latter, ridge-shaped maculae were noted in 9.2% of young subjects with myopia, an incidence that was markedly higher than that in our patients.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…Thus, it is possible that our patients were within the spectrum of ridge-shaped macula. However, there were several differences between the present study and the study by Xu et al [13]. In the latter, ridge-shaped maculae were noted in 9.2% of young subjects with myopia, an incidence that was markedly higher than that in our patients.…”
Section: Discussioncontrasting
confidence: 94%
“…Thus, this condition was considered as a distinct entity and labeled as "ridge-shaped macula." The authors suggested that ridge-shaped macula may be due to a folding of Bruch's membrane at the posterior pole, potentially caused by asymmetrical enlargement of that membrane in the equatorial region [13]. It is noteworthy that all the DSMs in our patients were also observed only on vertical OCT scan.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations